Drug administration through enteral tubes after gastrointestinal surgery (Research, Society and Development, 2021)
Patients undergoing gastrointestinal tract operations are complex and often receive medications via enteral tubes (ET). The aim of this study was to analyze the profile of the limitations of administration via SE of medications prescribed to patients undergoing operations on the gastrointestinal tract and abdominal wall and associated factors. To this end, all electronic prescriptions of patients using enteral nutrition (EN) and in the postoperative period at a general university hospital were analyzed (01/05 to 12/05/2017). Medicines prescribed for administration via ET were identified and a literature review about limitations for its administration in this type of tube. The prevalence of these limitations and associated factors was determined through uni (Pearson's chi-square) and multivariate (logistic regression - 5% statistical significance level) analyzes. A total of 341 prescriptions from 40 patients were analyzed. A total of 725 drugs prescribed via ET (44 different drugs) were identified. In the review, 33 articles were retrieved for the construction of a database, which allowed the identification of 188 limitations regarding drug administration via ET. The prevalence of at least one limitation regarding drug administration via ET among the patients evaluated was 57.5% (n = 23), and it was positively associated with age equal to or greater than 60 years (OR 4.67; 95%CI 1.07-20.40). Due to the scarcity of references for medication administration via ET, this study is an important tool for pharmacotherapeutic care for patients using EN. The number of limitations identified was low, but its association with advanced age and the severity of the studied population reinforce the importance of prioritizing its management.